2021
DOI: 10.1002/tax.12509
|View full text |Cite
|
Sign up to set email alerts
|

Vellozo's Florae Fluminensis: A new assessment of the São Paulo part of his collecting itinerary, its vegetation, and species list

Abstract: Our analysis of Vellozo's itineraries and his manuscript annotations show that ca. 1/4 of the names described in his Florae Fluminensis were based on plants collected in the municipality of Cunha, state of São Paulo. This region, within the Atlantic Forest domain, encompasses various vegetation formations, such as montane ombrophilous forests, mixed ombrophilous forests, and highaltitude open savanna enclaves. Using Vellozo's manuscripts, we traced his collecting itinerary, correlating his descriptive terms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The species was poorly described in Vellozo (1829) and the accompanying illustration in Vellozo (1831) depicts a sterile branch from a specimen growing in the municipality of Cunha, state of São Paulo ( Pastore et al 2021 ). According to Krukoff (1938) , it could represent either E. crista-galli L. or E. falcata Benth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The species was poorly described in Vellozo (1829) and the accompanying illustration in Vellozo (1831) depicts a sterile branch from a specimen growing in the municipality of Cunha, state of São Paulo ( Pastore et al 2021 ). According to Krukoff (1938) , it could represent either E. crista-galli L. or E. falcata Benth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Há muitos anos se discute a existência pretérita e remanescente de ilhas de Cerrado em meio a floresta atlântica do Vale do Paraíba (veja Ab'Saber 2017 para um resumo histórico dos principais trabalhos no tema). Provavelmente, o primeiro relato de fragmentos de Cerrado no vale do Paraíba tenha sido feito pelo Frei José Mariano da Conceição Veloso em sua obra intitulada Florae Fluminensis, entre os atuais municípios de Paraty (Estado do Rio de Janeiro) e Cunha (Estado de São Paulo) (Pastore et al 2021). Outros autores reportam a presença pretérita de campos cerrados em áreas úmidas, principalmente próximas ao rio Paraíba do Sul, em uma faixa estreita entre Jacareí e Guaratinguetá, além de manchas descontínuas entre Caçapava e Taubaté (Devide et al 2014).…”
Section: Discussionunclassified
“…bn.gov.br/acervodigital), which is a complete set of the original plates, bound in 11 volumes, with each plate identified by a unique catalogue number; and 2) the Archives of the Torre do Tombo, Lisbon (https://digitarq.arquivos.pt/results?t=florae+fluminensis), which is an incomplete set, with only volumes 6, 7, 8, 9, and 11, and with the drawings slighty different from those in the Manuscript Section of the Brazilian National Library. Pastore et al (2021) showed that the original plates in Lisbon are less precise than those in Rio de Janeiro. In the present taxonomic treatment, lectotypes were chosen from the original unpublished plates made for Florae Fluminensis kept in the Manuscript Section of the National Library of Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
“…Frei José Mariano da Conceição Vellozo (1742-1811) wrote the Florae Fluminensis, a floristic study of the state of Rio de Janeiro and contiguous areas in the state of São Paulo (Pastore et al 2021). The text of this multi-volume work was published posthumously in 1829, although the frontispiece reports "1825" as the publication date.…”
Section: Cephaelis Microcephalamentioning
confidence: 99%